Cultural intelligence and individual performance in global virtual teams - Aguilar Barrientos, Sara (2018)
The purpose of this research was to find the relationship that exists between cultural intelligence and contextual performance, when moderated by cultural diversity in global virtual teams. A sample of 215 employees from a multinational services company was used. Data analysis was performed using a multi-group invariance structural equation model (x2/df% = 1.22, p > .01; RMSEA = .05; CFI = .97; SRMR = .08). There was a positive and significant correlation between cultural intelligence and contextual performance, which led to accept hypothesis 1 (Group 1: H1, Y11=.52, p<.01; Y12=.74, p<..01. Group 2: Y1'=.28, p<.01; Y12=.39, p<.01). Categorical moderation revealed that a high cultural diversity, increases the relationship between the independent and dependent constructs, therefore hypothesis 2 was also accepted (H2, Y11=.52, Y12=.74 > Y11=.28, Y12=.39). This allowed concluding that having cultural intelligence impacts positively individual contextual performance in global virtual teams, and that the more culturally diverse people are in the work unit, the higher is this link.